Agglomeration Effects and the Location of Foreign Direct Investment – Evidence from French First-time Movers - Vivien Procher (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper analyzes the location choice determinants of French first-time investments in Europe, North America and North Africa. Firm locations are examined on two geographical scales, the national and regional level. The final sample comprises 307 location decisions in 27 countries and across 45 regions. Both, location- and firm-specific variables are used for analysing the investment strategy of French firms. The results show that higher market demand and cultural proximity to France increase the likelihood of a particular location to be chosen, whereas higher labour cost and a larger distance between a foreign location and the headquarters deter FDI investments. Manufacturing and older companies are more likely to establish their first subsidiary in Eastern Europe. Furthermore, this study examines the extent to which French investors choose foreign locations that already host a significant number of French firms. The results obtained from regressions with various absolute and relative agglomeration measures suggest that French investors are rather attracted by firm cluster in general, or by the unobserved factors that led to the agglomeration in the first place, than by any nation-specific firm cluster.
Keywords: F21; F23; D21; R30; 330; Foreign direct investment; location choices; agglomeration; small- and medium-sized enterprises; Direktinvestition; Standortwahl; Agglomerationseffekt; Klein- und Mittelunternehmen; Französisch; Deutschland